Early effects of LT3 + LT4 combination therapy on quality of life in hypothyroid patients: a randomized, double-blind, parallel-group comparison trial - Fatemeh Hajtalebi; Fariba Alaei-Shahmiri; Fatemeh Golgiri; Najmeh Shahini; Hamideh Akbari; Kasra Assadian; Seyedarad Mosalamiaghili (BMC Endocrine Disorders)
Abstract Background This study aimed to evaluate the impact of combined levothyroxine (LT4) and triiodothyronine (LT3) therapy on quality of life in patients with primary hypothyroidism. Methods In a randomized, double-blind, parallel-group trial, 151 Iranian patients diagnosed with primary hypothyroidism between 2020 and 2021 were enrolled. One group received LT4 alone (n = 80), while the other received LT4 and LT3 (n = 71) for a minimum of six months. The primary outcome was quality of life assessed using the SF-36V1 questionnaire, and the secondary endpoints included clinical and laboratory measurements. Results In the LT4 + LT3 group, a significant reduction in TSH levels (p < 0.05) was observed compared to baseline. While no significant differences emerged between the groups in terms of blood pressure, lipid profiles (except for low-density lipoprotein cholesterol), or body weight, there were notable improvements in physical functioning and bodily pain in the LT4 + LT3 group compared to the LT4 + placebo group. Compared with baseline, combination therapy significantly increased the physical component summary score after six months, but the difference was not significant. Conclusion Combination therapy may benefit patients with primary hypothyroidism, particularly those experiencing body pain or physical function issues. However, the overall impact on quality of life remains inconclusive, as evidenced by the scores for the mental component. Further research is needed to determine the broader implications of this therapy. This study provides valuable insights into the potential advantages of combining LT4 and LT3 in the management of primary hypothyroidism. Trial registration The study was registered with the Iranian Registry of Clinical Trials (IRCT) and assigned the registration number IRCT20200410047012N1 on 2022–08-07. Trial registration number: IRCT20200410047012N1. Date of registration: 2020–06-12.